Poetic Education and Ecocriticism. Los árboles by Elena Martín Vivaldi (2023)
This article raises the value and relevance of the poetic work of Elena Martín Vivaldi in relation to her worldview of nature. It explores through the studies of Literary Education and Ecocriticism to deepen in the proposal of didactic intervention in the classroom. The active and participative methodology starts by reading texts individually and leads to group discussion and literary creation tasks. The aim is to motivate students to consider literary reading and to develop their ecocritical awareness. This work is a proposal of didactic application in the secondary education classroom, which is important for the increasing of reading competence and the education of both personal and shared responsibility for conserving earth.